Air Quality in the Over the Bridge (OTB) Savin Hill Neighborhood of North Dorchester, MA. - O'Connor, Matthew. (2017)
Abstract: This thesis was an analysis of the Environmental Protection Agency's Criteria Air Pollutants (NAAQS) in the near highway neighborhood of Savin Hill "Over the Bridge" (OTB) in North Dorchester, Massachusetts. CO, NO2, SO2, O3, PM2.5 and PM10 concentrations were measured during the morning and evening rush hour commutes of Interstate 93 for 2 weeks in both the summer of 2007 and the winter of 2008. Meteorological and traffic influences were also assessed. Results demonstrated higher pollutants concentrations than allowed by the NAAQS during multiple sampling periods. Seasonal differences in concentrations of pollutants were observed. Variability between sampling sites differed markedly between pollutants. The prevailing wind direction placed the OTB neighborhood downwind of the highway pollutant emissions during both summer and winter sampling periods. Travel times between Braintree and Boston did not display an impact on pollutant concentrations.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Civil Engineering.; Advisor: Mark Woodin.; Committee: Anne Marie Desmarais.; Keywords: Environmental Health, Environmental Engineering, and Environmental Sciences.